Pattern of panic-buying and its psychosocial correlates among Pakistani adults during COVID-19 pandemic - Abbas, Kiran; Tahir, Amber; Raza, Aleena A.; Amreek, F. N. U.; Kumar, Jaish; Sakshi, F. N. U.; Aakash, F. N. U.; Asghar, Fahham; Haq, Inam U. (International Journal of Research in Medical Sciences, 2020)
Background: As the COVID-19 pandemic rages on, one bizarre yet ubiquitous human behavior has resurfaced. Globally, people have engaged in panic buying and hoarding (PBH). This irrational practice of panic buying is driven by deficient, manipulated news amid COVID-19 crisis. Methods: A cross-sectional study was conducted with Pakistani adults (≤18 years). Data was collected through an anonymous self-reported online survey from 17th April 2020 (0800 hours) through 20th April 2020 (2200 hours) via social media platforms. The survey consisted of sociodemographic characteristics, questions regarding food/essential supplies PBH and its psychosocial correlates- attitudes about COVID-19 severity (CA), values related to social responsibility (SR), social trust (ST), and self-interest (SI). Data was entered and analyzed using IBM Statistical package for social sciences (SPSS) version 20. Results: There were 786 participants in the survey; 59% were females. Mean age was 26.6±7.6 years. Mean PBH score was 2.31±0.85 (range: 1-5). Overall, 28.4% hoarded supplies a few times or more and 47% agreed to have bought more food/essential supplies due to COVID-19. Correlation analysis showed a 12.3% positive correlation of PBH with ST and 8.5% positive correlation with SI (p<0.05). In the multivariate regression model, PBH showed a statistically significant (p<0.05) positive impact on ST and SI. Conclusions: More than one-fourth of the individuals indulged in panic buying and hoarding during the COVID-19 in Pakistan. Fear of contracting the virus and uncertainty about the duration of lockdown was the common reasons behind PBH. Social trust and self-interest were significant psychosocial contributors to hoarding behavior.